The Role of Fear of Missing Out in Mediating the Effect of Social Media Addiction on Impulse Buying in Fashion Products - I Gusti Ngurah Anom Mahaputra; Ni Made Asti Aksari (International Forum of Researchers and Lecturers, 2025)
The development of digital technology and the massive penetration of social media have transformed consumption patterns, particularly among younger generations. Excessive use of social media may lead to addictive behavior, which has the potential to trigger psychological anxiety such as fear of missing out, and ultimately encourage impulse buying behavior. Denpasar City, as a center of urbanization and consumption in Bali, serves as an appropriate location to examine this phenomenon, as its community tends to be consumptive and highly active in social media use. The purpose of this study is to explain the role of fear of missing out in mediating the effect of social media addiction on impulse buying. This study employs Uses and Gratifications (U&G) theory as the theoretical foundation, with a sample of 130 respondents selected using purposive sampling. Data collection was conducted through a questionnaire method. The study applied descriptive and inferential techniques, including Path Analysis, Classical Assumption Test, and Sobel Test. The findings reveal that fear of missing out mediates the effect of social media addiction on impulse buying. This study strengthens the understanding that social media not only influences social interaction but also shapes impulsive consumption behavior as a result of psychological pressure and exposure to digital content.